2010
DOI: 10.1093/jac/dkq345
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin modulates the colonic microbiota of patients with Crohn's disease: an in vitro approach using a continuous culture colonic model system

Abstract: We demonstrated that rifaximin, while not altering the overall structure of the human colonic microbiota, increased bifidobacteria and led to variation of metabolic profiles associated with potential beneficial effects on the host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
118
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(137 citation statements)
references
References 55 publications
11
118
0
8
Order By: Relevance
“…It was even shown to increase the fraction of potentially protective bacteria such as various species of the genera Bifidobacterium and Atopobium of the class Actinobacteria and Faecalibacterium prausnitzii of the Clostridium cluster IV. 11 Further, rifaximin promotes the production of short-chain fatty acids, which are capable of inducing regulatory T cells. 11 In addition, it modulates intestinal inflammation by reducing the expression of bacterial virulence factors, adhesion and epithelial internalization of pathogens and inflammatory cytokine production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was even shown to increase the fraction of potentially protective bacteria such as various species of the genera Bifidobacterium and Atopobium of the class Actinobacteria and Faecalibacterium prausnitzii of the Clostridium cluster IV. 11 Further, rifaximin promotes the production of short-chain fatty acids, which are capable of inducing regulatory T cells. 11 In addition, it modulates intestinal inflammation by reducing the expression of bacterial virulence factors, adhesion and epithelial internalization of pathogens and inflammatory cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…11 Further, rifaximin promotes the production of short-chain fatty acids, which are capable of inducing regulatory T cells. 11 In addition, it modulates intestinal inflammation by reducing the expression of bacterial virulence factors, adhesion and epithelial internalization of pathogens and inflammatory cytokine production. [21][22][23] It has been reported that rifaximin is able to modulate intestinal Figure 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 Concentrated in the gut, rifaximin is presumed to modulate intestinal bacteria, thereby reducing intestinal ammonia and toxin formation. 42 In a recent open labeled trial, Bajaj et al performed a systems biologic analysis of the microbiome and evaluated cognitive changes after treatment with rifaximin (550 mg bid) in 20 cirrhotic patients diagnosed with MHE. Therapy was associated with improved cognitive function and reduced endotoxemia.…”
Section: Rifaximinmentioning
confidence: 99%
“…Several studies have demonstrated the positive effects of rifaximin on the composition of the gut microbial community, and in particular the increase in the abundance of bacteria associated with health such as Bifidobacterium, F. prausnitzii, and Lactibacillus, in the absence of significant alterations of the overall composition, lasting up to 1 month after treatment completion [4][5][6].…”
mentioning
confidence: 99%